The effect of sports teachers' social responsibility on optimizing leisure time and preventing students' social harms - shahab bahrami; mohammad saeid kiani; leila nazari; Leila shahbazpour (Institute of Management fekrenoandish, 2021)
Extended Abstract Abstract The aim of this study was to investigate the effect of social responsibility of sports teachers on optimizing leisure time and preventing social harms of students. The study method was descriptive- correlative. The statistical population of the study included all 2950female high school students in the seventh district of Tehran. The sample size was determined based on Krejcie and Morgan table of 370 students who were selected by means of cluster random sampling method. Data collection tools included the standard questionnaire of Barton Goff (2012), the researcher-made questionnaire of Kashefi and Nazari (2018) and the questionnaire of Aaghaii and Timurtash (2009). The validity of the questionnaires in terms of form and content was confirmed by sports management professors and their reliability was confirmed by Cronbach's alpha coefficient test. Data analyzing was accomplished by Spss statistical software. Findings showed that the social responsibility of sports teachers is effective in optimizing students' leisure time and social harms. Furthermore, leisure time is effective in preventing students' social harms. Favorable ‌ spending of leisure time ‌ in a comprehensive and essential form ‌ ‌ ‌allows young people ‌ to meet the aspects of life; ‌ experience of teamwork; ‌ skills; ‌ and design a bright and promising future. Introduction Various activities are performed in the education system for the growth and excellence of individuals and bringing human beings to the desired perfection; including educational, research, cultural, social, athletic, etc. (Ahmadi & et al, 2020). Today, social responsibility goes far beyond its field of activity and influence in the past, which was humanitarian. Social responsibility has found its role and place in the field of business to achieve sustainable development, on preventive solutions to the social and environmental challenges and similar areas (Chau & et al, 2018). Therefore, one of the most important indicators and components of social growth is social responsibility (Commentary & et al, 2019). Responsibility is obligation and inner commitment of the individual in the proper performance of all activities entrusted to her (Ester Cerin & et al, 2017). On the other hand, sometimes, there is a kind of confusion accompanied by a decrease in self-esteem and self-concept during a special and sensitive period of adolescence, which leads to a decrease in natural activities and social interactions. Therefore, the adolescent can be prepared to learn ethical concepts by being taught responsibility and assigning appropriate plans to him/her (Faith & et al, 2016). Participation in sports activities is one of the educational activities during which the students can develop characteristics such as responsibility, cooperation and social relations (Ghalavandi & et al, 2018). Nowadays, some concerns of parents and teachers are optimal learning and correct education and avoidance of social harms of students, and there are many ways to achieve these goals, including all kinds of encouragement and laziness, and visiting doctors and psychologists, and etc., nontheless few people have tried the effect of exercise on learning and reducing social harms. Also, in our country, less attention is paid to students' leisure time, and the reason is that leisure time has not yet found its real place in society. The plans of education officials and families and the responsibility of teachers, especially physical education teachers, are not enough for students' leisure time and do not provide them with satisfaction. Accordingly, the responsibility of teachers, who have an effective role in reducing the social harms of students in their spare time, is felt more. According to the contents of this article, an attempt is made to answer the question that how far the sport teachers are effective on optimizing leisure time and preventing social harms of students? Theoretical framework Inadequate and unfavorable social results are obtained when "leisure" is not designed for attractive, fun and uplifting programs full of "educational" elements. Spending this time in the context of healthy activities can reduce its harmful aspects and be a preventive measure against adolescents going astray on these ages (Mehrdad, 2011). A study by Yen et al. Found that adolescents who spend their leisure time with friends in "unsupervised activities" are more likely to exhibit "aggressive" behaviors than adolescents who are "organized" and "active" during leisure time and also indoor activities (Khwaja Nouri & Hasheminia. 2010). In a study Hosseini and Mirzaei Khalis (2021) examined the mediating role of social goals in the relationship between mental vulnerability and responsibility in female high school students, and the results showed that there is a positive and significant relationship between students' psychological vulnerability and their social goals responsibility. (Hosseini and Mirzaei Khalis, 2021). Methodology The present study is methodically descriptive-correlative. The statistical population of this study includes statistically 2950 female high school students in the seventh district of Tehran, of which 370 students were selected as a research sample by cluster random sampling. The validity of the questionnaires was determined by the point views of sports management experts and so were the questionnaires approved. The reliability of the questionnaires in this study was determined by Cronbach's alpha. The Cronbach's alpha coefficient of the social responsibility, leisure and social harm questionnaires were 0.75, 0.85 and 0.86, respectively, which has the desired reliability of the questionnaires. Descriptive statistics such as central indicators were used to analyze the data and correlation coefficient and regression were used to measure the relationship between variables. Discussion and Results The camera-Watson test was used to test the research hypotheses. Considering the value of simple correlation coefficient, it can be said that sport has an effect on optimizing the leisure time of female high school students in the seventh district of Tehran (R = 0.146). Also, the social responsibility of sports teachers has an effect on the prevention of social harms of female high school students in the seventh district of Tehran (R = 0.253). Leisure time also has an effect on the prevention of social harms of female high school students in the seventh district of Tehran (R = 0.351). Conclusion The aim of this study was to investigate the effect of social responsibility of sports teachers on the optimization of leisure time and prevention of social harms of students. Researches in the field of social responsibility can be referred such as Modarres Yazdi et al. (2020), Taghvai Yazdi (2016), Qalavandi et al., and in the field of leisure time, such as Hdayyan and Dodkhah (2020), Tamizifar & Azizifar (2021), Khater Wisie and Yektayar (2020), Mousavi Rad and Keshavarz (2018), Ester et al. (Ester, & Eva, 2020), Chau et al. (2018). Research results show that the variables of social responsibility and leisure are effective as two factors. Therefore, the results of this study indicate that the social responsibility of sports teachers is directly related to students 'leisure time. Therefore, leisure time not only prevents the spread of social anomalies, but also helps the students' development in a way that they feel responsible towards the community and peers, so leisure activities for a student are conditions for trial and error and social experience that allows him to enter the community and take responsibility. Among the limitations of the present study, it can be mentioned that during the present study the researcher found that other variables (economic-facilities, cultural-social, and family and personal factor) are effective in preventing social harms, but in the present study it has been assumed to be constant. Sports can have a significant effect on the vitality of male and female students. Students who are in a better mental condition are undoubtedly safe from most social ills such as addiction and sexual perversion. These students, healthy and vital. are more successful in other stages of life, (A healthy mind in a healthy body) and they will be successful parents in the future.